Female Adolescents and Young Adult Consumers' Affinity for Online Flash Sales Concept in India: A Triangulation Approach - Vashishta, Deblina Saha; Chadichal, Shilpa Santosh (Indian Journal of Marketing, 2012)
Modern day marketers have a tremendous opportunity to connect to women in a better way with the products they buy and the media technologies they use to make a positive impact in their lives. After a strong and immense growth in 2010, internet retailing just came shining ahead of all other retailing channels and emerged as a strong winner even after recession, driven by shifting consumer attitudes and mindsets. Remarkable transformation in economic independence, better access to education, better and improved career opportunities and higher pay scales in both developed and emerging economies have been some of the major factors responsible for the transformation of women into smart and intelligent consumers. Online flash sales sites are the latest buzz in India that have come up in response to rising investor interest in private sale portals across the globe such as the Gilt Group and Rue LaLa in USA and Ventee-Privee.Com in Europe. Today, the flash-sale shopping sites have their own loyal following, and the range of products offered varies from fashion to electronic gadgets to apparels to loads of other categories. The fact that shopping behavior varies not only between men and women, but is quite different between the women of different countries, religions and even age groups intrigued the researchers to get a deeper insight about the young female consumers' psyche and attitude regarding the online flash sales hype in India.